2010
DOI: 10.2528/pier10052408
|View full text |Cite
|
Sign up to set email alerts
|

Through-the-Wall Target Localization With Time Reversal Music Method

Abstract: Abstract-Time Reversal Multiple Signal Classification (TR-MUSIC) method is studied and adapted for the detection and localization of multiple targets behind the wall in this paper. TR-MUSIC does not involve the FDTD solver for the implementation of the backpropagation of the time reversed field and is very computational efficient. The Green's function vectors for the computation of the TR-MUSIC pseudo-spectrum is efficiently evaluated with the saddle point method for a homogeneous wall. By employing the null s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 29 publications
0
67
0
Order By: Relevance
“…However, these two types of radar are difficult to be applied in the non-line-of-sight (NLOS) scenes due to the poor penetrability. To improve the penetrability of nonmetallic obstacle, ultra-wideband (UWB) radar has been employed to detect vital sign of the victims in the NLOS scenes [9][10][11][12][13][14][15][16]. In these scenes, it mainly focuses on whether the victim is alive [16][17][18][19][20][21][22][23], namely life detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, these two types of radar are difficult to be applied in the non-line-of-sight (NLOS) scenes due to the poor penetrability. To improve the penetrability of nonmetallic obstacle, ultra-wideband (UWB) radar has been employed to detect vital sign of the victims in the NLOS scenes [9][10][11][12][13][14][15][16]. In these scenes, it mainly focuses on whether the victim is alive [16][17][18][19][20][21][22][23], namely life detection.…”
Section: Introductionmentioning
confidence: 99%
“…TR was introduced by Mathias Fink in 1992 for ultrasonic imaging and later widely utilized in several ultrasonic applications such as transcranial therapy [1]. It was extended into the realm of electromagnetics by Lerosey et al [2] and has shown a lot of progress in ultra-wideband (UWB) applications involving radar detection in cluttered media [3] and non-destructive evaluation [4]. Research on using microwave TR for imaging has been limited over the years, but warrants renewed study because of its advantages over conventional imaging systems.…”
Section: Introductionmentioning
confidence: 99%
“…These achievements revealed that TR-MUSIC can be applied to extended targets as same as point targets and the shape details can be obtained. Furthermore, TR-MUSIC algorithm can be used to other applications, such as through-the-wall imaging (TWI) [15] and surveillance in wireless sensor network [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in radarbased imaging, signal processing techniques are employed to identify only the regions with stronger backscattering, which indicate the presence of a contrast in electrical properties. Many signal processing methods have been adopted to complete this task, including wavefront reconstruction [4], delay and sum (DAS) beamformer or confocal microwave imaging (CMI) [5][6][7], microwave imaging via space-time (MIST) beamforming [8], multi-input multi-output (MIMO) radar processing techniques [9], and subspace-based Time-reversal MUtiple SIgnal Classification (TR-MUSIC) algorithm [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%